2005
DOI: 10.1161/01.hyp.0000185148.27901.fe
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 (ACE2) and ACE Activities Display Tissue-Specific Sensitivity to Undernutrition-Programmed Hypertension in the Adult Rat

Abstract: Abstract-Human epidemiological studies have shown that low birth weight is associated with hypertension in adulthood.Rodent models of intrauterine growth retardation (IUGR) support these findings because offspring from undernourished dams develop hypertension. Angiotensin-converting enzyme 2 (ACE2) is a newly described renin-angiotensin system (RAS) component that competes with ACE for angiotensin peptide hydrolysis and therefore may modulate blood pressure. However, ACE2 potential participation in hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
96
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 41 publications
6
96
1
4
Order By: Relevance
“…51 Previous studies have demonstrated an activation of the renin-angiotensin system in MUN offspring. 52 Furthermore, the adrenal expression of angiotensin receptor 1b is increased in these offspring, 53 suggesting increased responsiveness of the adrenal to circulating angiotensin II. Elevated angiotensin II levels and increased responsiveness to its effects in MUN offspring would be expected to stimulate the expression of CYP11A1 mRNA as demonstrated by our data.…”
Section: Discussionmentioning
confidence: 94%
“…51 Previous studies have demonstrated an activation of the renin-angiotensin system in MUN offspring. 52 Furthermore, the adrenal expression of angiotensin receptor 1b is increased in these offspring, 53 suggesting increased responsiveness of the adrenal to circulating angiotensin II. Elevated angiotensin II levels and increased responsiveness to its effects in MUN offspring would be expected to stimulate the expression of CYP11A1 mRNA as demonstrated by our data.…”
Section: Discussionmentioning
confidence: 94%
“…These studies confirmed that impaired fetal development has long-term metabolic consequences, sensitizing the offspring to hyperphagia and obesity, particularly when they are fed a hypercaloric diet (22,26,53), reduced leptin and insulin sensitivity (10,26,50,51), type 2 diabetes (43), and elevated blood pressure (32,44). In adults, the pivotal role of the hypothalamus, especially the arcuate nucleus (Arc), in the maintenance of energy homeostasis controlling the nutritional status and energy storage level is well established (45).…”
mentioning
confidence: 76%
“…Using a model of prenatal maternal 70% food-restricted diet (FR30) in rats throughout gestation, we previously showed that FR30 induces IUGR and programs some metabolic syndrome features in adult male rat offspring (44). We hypothesized that prenatal maternal FR30 induces developmental programming that durably modifies levels of key circulating factors acting on the hypothalamus, as well as hypothalamic gene expression, in adult offspring.…”
mentioning
confidence: 99%
“…10,15,16 In experimental studies, first, in knockout mice lacking the ACE2 gene, blood pressure is either normal or only mildly increased compared with control littermates. 5,9,17 In rats, Pendergrass et al 18 found that hypertensive male mRen2.Lewis rats had lower cortical ACE2 activity than normotensive Lewis rats, but no difference in ACE2 activity was present between female hypertensive and normotensive rats in the same study.…”
Section: Controlsmentioning
confidence: 99%